PERSEPSI WAJIB PAJAK UMKM TERHADAP PERATURAN PEMERINTAH NO.46 TAHUN 2013 PADA KPP PRATAMA TAMPAN PEKANBARU - Dyta Rusdianna Dyta Rusdianna; Suarman Suarman '; RM Riadi RM Riadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims to determine the level of knowledge and perception of the taxpayer about the Regulation of Government Number. 46 year 2013, which is related to tariff and tax base and simplification in collecting tax. The population in this study is taxpayer with a turnover under Rp 4.8 billion which have been registered in the KPP Pratama Tampan Pekanbaru. The research data is obtained from questionnaires distributed to taxpayers of UMKM the informants in this study. The data is analyzed by using descriptive data analysis. Base on the results of study, it concluded that: perception of the taxpayer about Regulation of Government Number. 46 year 2013 is generally good enough category. From the four principles of in taxation, the respondents have a good perception in efficiency principle. While in the principle of Equality, Certainty, and Convenience, they have a good enough perception so that it clarified that the respondents consider this regulation does not really deal with the principles. The suggestion is socialization should be given thoroughly until the districts level and KPP should make a best partnership with the third party related to UMKM to provide a knowledge and understanding to the taxpayer.Keywords: Perception, UMKM, Regulation of Government Number. 46 year 2013